2019
DOI: 10.1007/s42413-019-00020-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Relationship between Income and Infectious Disease: Evidence from Cameron County

Abstract: The environments in which people are born, live, learn, work, play, worship, and age affect a wide range of health, functioning, and quality-of-life outcomes and risks. Research on poverty indicates that lower income is linked to poorer health. The lower an individual's income, the higher is his or her likelihood of disease and premature death. Furthermore, some research indicates that a higher risk of contracting an infectious disease may exist for those living in poverty. This study explored the potential ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The increased income will promote the public's well-being and further promote their health, as it greatly empowers an individual's ability to afford healthcare. Some research has indicated that a higher risk of contracting an infectious disease may exist for those living in poverty ( 63 , 64 ). Through the advanced development of ICTs, the capacity to improve health system efficiencies will be greatly increased and medical errors will be significantly reduced.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…The increased income will promote the public's well-being and further promote their health, as it greatly empowers an individual's ability to afford healthcare. Some research has indicated that a higher risk of contracting an infectious disease may exist for those living in poverty ( 63 , 64 ). Through the advanced development of ICTs, the capacity to improve health system efficiencies will be greatly increased and medical errors will be significantly reduced.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Thereby, the improvement of income reducs the occurrence and spread of infectious diseases. There is a negative correlation between income levels and the incidence and prevalence of infectious diseases (Scarbrough and Holt et al, 2019). For example, conditions such as income levels in cities are generally better than those in rural areas, which makes urban prevention and control capability is higher than in rural areas(UNDP and TheChinaInstituteforReformandDevelopment, 2008; Alirol and Getaz et al, 2011).…”
Section: Incomementioning
confidence: 99%